Tinjauan Proses Pembuatan Laporan Internal Rekam Medis Di Rumah Sakit Umum Anna Medika Madura - Angga Ferdianto; Nutfah Kamila; Rivaldi Indra Nugraha (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2021)
Background: Internal reports of medical records are reports that are made as input to formulate the basic design concept of a hospital management information system. The accuracy of filling in the internal reports of medical records at Anna Medika Madura's Hospital is 60% out of 100%. The purpose of study is to review the process of making internal reports on medical records at Anna Medika Madura General Hospital Subjects and Method: This research design used descriptive method with a qualitative approach. The subjects of study were reporting officers and medical record officers, while the object of study were the internal reports of medical record and the process of making internal reports of medical records. How to collect data observation and interviews. The technique used purposive sampling. Results: Inaccuracies of internal reports of medical records up to 40% in the operating room unit, 50% in the labor room unit, and 30% in the daily census, so that the inaccuracy of internal reports of medical record must be controlled. The inaccuracy factor was that there were still officers who are inconsistent (man), and there was no SOP (method), and has been fulfilled (machines), which had a negative impact on the process on internal reports of medical records. Conclusion: Supposed to make SOP related to the preparation, control, and accuracy of filling internal medical records, conducting evaluations and disseminating information to officers regarding the importance of accuracy in filling internal medical records. Keywords: Accuracy, Delay, Internal reports of medical record.